Esotericism in African American Religious Experience: There Is a Mystery - Finley, Stephen; Guillory, Margarita; Page, Hugh R. ca. 20. Jh. (Aries book series, 2015)
Esotericism in African American Religious Experience: "There is a Mystery"…, brings together groundbreaking essays that inaugurate Africana Esoteric Studies (AES): a new trans-disciplinary enterprise that investigates esoteric lore and practices in Africa and the African Diaspora